Favorable effect of renal denervation on elevated renal vascular resistance in patients with resistant hypertension and type 2 diabetes mellitus - Manukyan, Musheg; Falkovskaya, Alla; Mordovin, Victor; Pekarskiy, Stanislav; Zyubanova, Irina; Solonskaya, Ekaterina; Ryabova, Tamara; Khunkhinova, Simzhit; Vtorushina, Anastasia; Popov, Sergey (Frontiers in Cardiovascular Medicine, 2022)
Objective To assess the effect of renal denervation (RDN) on renal vascular resistance and renal function in patients with drug-resistant hypertension (HTN) and type 2 diabetes mellitus (T2DM). Materials and methods Fifty-nine patients (mean age 60.3 ± 7.9 years, 25 men) with resistant HTN [mean 24-h ambulatory blood pressure (BP) 158.0 ± 16.3/82.5 ± 12.7 mmHg, systolic/diastolic] and T2DM (mean HbA1c 7.5 ± 1.5%) were included in the single-arm prospective study and underwent RDN. Renal resistive index (RRI) derived from ultrasound Doppler; estimated glomerular filtration rate (Chronic Kidney Disease Epidemiology Collaboration formula), office and 24-h ambulatory BP were measured at baseline, 6, and 12 months after RDN to evaluate the respective changes in renal vascular resistance, renal function, and BP during treatment. Results Forty-three patients completed 12 months follow-up. The RRI changed depending on the baseline value. Specifically, the RRI decreased significantly in patients with elevated baseline RRI values ≥ 0.7 {n = 23; −0.024 [95% confidence interval (CI): −0.046, −0.002], p = 0.035} and did not change in those with baseline RRI < 0.7 [n = 36; 0.024 (95% CI: −0.002, 0.050), p = 0.069]. No significant change was observed in eGFR whereas BP was significantly reduced at 12 months after RDN by −10.9 (95% CI: −16.7, −5.0)/−5.5 (95% CI: −8.7, −2.4) mmHg, systolic/diastolic. No relationship was found between the changes in RRI and BP. Conclusion Our study shows that RDN can decrease elevated renal vascular resistance (RRI > 0.7) and stabilize kidney function in patients with RHTN and T2DM independently of its BP-lowering effect.